Synthesis of virgin coconut oil esters and formation of nanoemulsions containing copper peptide for cosmeceutical use - Samson, Shazwani (2017)
Virgin coconut oil esters (VCOE) were synthesized enzymatically through alcoholysis reaction of virgin coconut oil (VCO) and oleyl alcohol. The properties of the esters showed their suitability to be used as cosmetic’s ingredient and exhibited non-irritant effect with a Human Irritancy Equivalent (HIE) score below 0.9. Factors (enzyme amount, reaction time, substrate molar ratio) that influenced the percentage yield (%) of esters were investigated using artificial neural network (ANN) and the optimum percentage yield obtained was 96.05%. Pseudo-ternary phase diagrams for VCO/surfactant/water and VCOE/surfactant/water systems were constructed to serve as platform in building the emulsion systems. Surfactants used were mixture of Tween 80 (T80) and Pluronic F68 (PF68) at ratio of 40:1. Based on the results, multiphase regions dominated the two pseudo-ternary phase diagrams. Therefore, several compositions with low surfactants contents from the multiphase regions of the pseudo-ternary phase diagrams were selected for modification, by incorporating xanthan gum as stabilizer into the system. Xanthan gum was found to be able to stabilize the emulsions systems where smaller particle size was obtained at high concentration of surfactant and low concentration of oil and xanthan gum. The effect of composition on nanoemulsion; VCO, T80:PF68 and xanthan gum on variation of particle size was investigated using D-optimal Mixture Design and ANN. The particle size of nanoemulsions estimated by D-optimal was 120.88 nm while ANN was 124.16 nm. The most suitable method for optimizing the nanoemulsions systems was found out to be ANN due to the lower percentage of residual standard error (RSE). The optimum compositions obtained for VCO nanoemulsion were VCO (10.00%, w/w), T80:PF68 (15.00%, w/w), xanthan gum (0.87%, w/w) and water (74.13%, w/w). The same composition was used for the preparation of VCOE nanoemulsions since there was no significant difference observed in term of particle size. Incorporation of copper peptide in the optimum formulations also showed insignificant effect on the particle size. Physicochemical characterization and stability evaluation were conducted for the optimum VCO and VCOE nanoemulsions without active (Opt-VCO and Opt-VCOE, respectively) and with the addition of active (VCOCP and VCOECP, respectively). Final formulations were found out to be in ‘nano’ sized with good stability and were proven to be the oil-in-water type of nanoemulsions with pH suitable for human skin. The micrographs obtained using Transmission Electron Microscopy (TEM) showed that the particle size was in agreement with the measured size. The final formulations exhibited pseudoplastic properties, shear thinning behavior and elastic behavior where wide linear viscoelastic region was observed which correlated well to the high rigidity of the system. In the stability study, the final nanoemulsions showed excellent physical stability against centrifugation test, freeze-thaw cycle test and storage at temperature 25 °C and 45 °C for 90 days. In-vitro permeation study indicated the ability of the nanoemulsions to improve the permeability of copper peptide as compared to control. The percentage amount of copper peptide that permeates through skin barrier was observed to be higher for VCOE nanoemulsion as compared to VCO nanoemulsion. In the cytotoxicity test, nanoemulsions showed no cytotoxicity effect on fibroblast cells (3T3) with IC50 value higher that 1000μg/ml. The short-term moisturizing effect on 10 subjects showed increment in skin hydration and reduction of TEWL after application of formulations Opt-VCO and Opt-VCOE. Opt-VCOE exhibited higher skin hydration value after application of the cream to subject’s skin. Due to the higher moisturizing capacity of Opt-VCOE as compared to Opt-VCO, VCOE-based nanoemulsion containing copper peptide (VCOECP) was selected for the anti-aging efficacy study. In the irritancy test, VCOECP was found out to be non-irritant with HIE scores lower than 0.9. Anti-aging efficacy measurements showed increment in skin hydration and reduction of the transepidermal water loss (TEWL) after application of VCOECP and placebo. Higher skin hydration value and lower TEWL value was observed for VCOECP as compared to placebo. The mean collagen score was increased significantly from 24.92 ± 4.32 to 41.67 ± 5.57 after application of copper peptide nanoemulsion as compared to at day 0. Placebo did not show any possible therapeutic effect on collagen since there was no significant increment in collagen score from day 0 to day 28. No visible skin reactions were experienced by the subjects during treatment. This work concluded that stable VCO and VCOE nanoemulsions having moisturizing properties and fit for cosmetic use were successfully developed. Copper peptide loaded nanoemulsion showed collagen regeneration in human skin and thus exhibited potential use in the cosmeceutical industry.